Implementation of Interactive Workshops with Mentimeter, Crossword Puzzle, and Wordwall in the Professional Development of Teachers at SMAN 1 Sajingan - Sulistyarini Sulistyarini; Imran Imran; Ika Rahmatika Chalimi; Stella Pransisca; Yusawinur Barella; Venny Karolina; Edwin Mirzachaerulsyah; Hendra Hendra; Vionaria Vionaria; Fajar Adilah Pratama (I-Com: Indonesian Community Journal, 2024)
Faculty of Teacher Training and Education, Tanjungpura University, carried out community service entitled "Interactive Workshop with Mentimeter, Crosswords and Wordwalls for Teachers at SMAN 1 Sajingan Border Malindo". The school's location on the Indonesia-Malaysia border demands education that is globally competitive. However, challenges such as limited infrastructure and lack of teacher training are obstacles. Therefore, the aim of this workshop is to increase the teachers profesionalism at SMAN 1 Sajingan through assessing the more interactive and innovative learning by utilizing digital platforms such as Mentimeter, Crosswords, and Wordwall. This activity includes training, interactive discussions, and guidance in designing participatory assessments. Evaluation of the activity shows a significant increase in teacher competence in developing innovative assessment, with more than 60% of participants agreeing and 30% strongly agreed that this workshop increased teacher competency and benefited directly from the series of workshops. Participants hope for longer and more sustainable training sessions.